Safety of ambroxol in the treatment of airway diseases in adult patients - Cazan, Dorotheea (Expert opinion on drug safety, 2018)
Introduction: Ambroxol is a widely used secretolytic and mucoactive over-the-counter agent primarily used to treat respiratory diseases associated with viscid mucus. Following post-marketing reports of hypersensitivity reactions and severe cutaneous adverse reactions (SCARs) possibly linked to ambroxol, the European Union’s Pharmacovigilance Risk Assessment Committee (PRAC) initiated in April 2014 a review of the safety of ambroxol in all its registered indications, which was finalized in 2016.Areas covered: Here, we evaluate the clinical safety of ambroxol and provide an expert opinion on the benefit-risk balance of ambroxol in the treatment of adult patients with bronchopulmonary diseases. The evidence for this review is derived from clinical trials of ambroxol that were provided to the PRAC by the marketing authorization holders of ambroxol-containing medicines.Expert opinion: Clinical experience accumulated from randomized clinical trials and observational studies suggests that ambroxol is a safe and well-tolerated treatment of bronchopulmonary diseases, with a well-balanced and favorable benefit-risk profile. All reported adverse events were mild and self-limiting, and the risk of SCARs with ambroxol is low. Further investigations could address the safety and efficacy of ambroxol in pediatric lung diseases and in additional therapeutic indications, such as biofilm-dependent airway disease and lysosomal storage disorders.